Fast continuous energy scan with dynamic coupling of the monochromator and undulator at the DEIMOS beamline. (17th March 2014) - Joly, L.; Otero, E.; Choueikani, F.; Marteau, F.; Chapuis, L.; Ohresser, P.
<x xml:space="preserve">Abstract</x> In order to improve the efficiency of X‐ray absorption data recording, a fast scan method, the Turboscan, has been developed on the DEIMOS beamline at Synchrotron SOLEIL, consisting of a software‐synchronized continuous motion of the monochromator and undulator motors. This process suppresses the time loss when waiting for the motors to reach their target positions, as well as software dead‐time, while preserving excellent beam characteristics.